Protection and degradation integrated permselective membrane material and preparation method thereof
The poor selectivity of existing protective film materials is solved by using polyvinylidene fluoride main chain and grafted imidazole-imidazole-4-vinylbenzylchloride polymerization in chemical protective clothing. The problem of this problem has achieved effective barriers to chemical warfare agents and water vapor transmission, improving the protection and comfort of protective clothing.
Patent Information
- Application Number
- CN202411475467.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-17
AI Technical Summary
The protective film materials of existing chemical protective clothing have poor selectivity and average protective effect, and cannot effectively block chemical warfare agents and allow water vapor to pass through, resulting in dangers such as heat accumulation and dehydration of the wearer.
The protective degradation integrated selection of permeable membrane materials is used to form a polyvinylidene fluoride main chain and a grafted imidazolized 4-vinylbenzylchloride polymerized side chain, and the OH-type membrane materials are prepared by a specific preparation method. Improve moisture permeability and disinfection capabilities, and achieve protection and degradation of chemical warfare agents.
The membrane material has excellent selective permeability and degradation ability, and the water transmittance reaches 3130g m-224h-1. It can effectively block chemical warfare agents, avoid the harm of damp heat stress reactions to the human body, and has good mechanical properties and degrading chemical warfare agents.
Smart Images

Figure CN119143933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical protection, and in particular relates to a selectively permeable membrane material integrated with protection and degradation for chemical protective clothing and a preparation method thereof. Background Art
[0002] Chemical protective clothing (CPC) is used to protect human skin from harmful chemicals. Traditional chemical protective clothing is usually based on insulating materials such as butyl rubber and halogenated butyl rubber, which can completely block all vapor and liquid penetration. However, this kind of protective clothing will also block the path of vapor transmission, which can easily cause heat accumulation in the wearer, and in severe cases, it can cause dehydration, fainting, and even death. On the other hand, adsorption fabrics with activated carbon adsorbents have also been used for chemical protection. Although better physiological comfort can be achieved, there are still defects such as limited adsorbent capacity, high weight, and secondary pollution caused by desorption.
[0003] The ideal chemical protective clothing should have reliable protection and ideal water vapor permeability, blocking chemical warfare agents (CWA) while allowing water vapor to pass through. It is generally believed that the ideal water vapor permeability of chemical protective clothing is 1500-2000g m -2 24h -1 The Journal of Membrane Science, 2010, 362 (1-2): 137 reported a polystyrene sulfonic acid (PSSA) membrane material, which has good selective permeability, but has poor mechanical properties. The Journal of Physical Chemistry B, 2004, 108 (26): 8900 studied the selective permeability of the commercial perfluorosulfonic acid membrane Nafion, indicating that Nafion has the potential to be used in chemical protective clothing, but has the disadvantage of high cost of Nafion materials. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] The present invention provides a selective permeable membrane material integrated with protection and degradation and a preparation method thereof, so as to solve the technical problems of poor selectivity and general protection effect of existing protective membrane materials.
[0006] (II) Technical solution
[0007] In order to solve the above technical problems, the present invention provides a selective permeable membrane material with integrated protection against degradation. The selective permeable membrane material with integrated protection against degradation is composed of a polyvinylidene fluoride main chain and a grafted imidazolylated 4-vinylbenzyl chloride polymerized side chain.
[0008] In addition, the present invention also provides a method for preparing a selectively permeable membrane material with integrated protection against degradation, and the method for preparing a selectively permeable membrane material comprises the following steps:
[0009] S1. 4-vinylbenzyl chloride and imidazole are mixed and stirred to prepare imidazole 4-vinylbenzyl chloride monomer, and N,N-dimethylformamide is added to dissolve the monomer to obtain a first mixed solution;
[0010] S2. The polyvinylidene fluoride powder is added to the first mixed solution and stirred to dissolve to obtain a second mixed solution;
[0011] S3. The methanol solution of tetramethylammonium hydroxide is added to the second mixed solution and stirred to obtain a third mixed solution;
[0012] S4. The crosslinking agent and the initiator are added to the third mixed solution to obtain a polymer solution;
[0013] S5. The polymer solution is heated under nitrogen protection to obtain a selectively permeable basement membrane solution;
[0014] S6. The selective permeable base membrane solution is poured onto a glass plate and dried to obtain a selective permeable base membrane material;
[0015] S7. Soak the selective permeable base membrane material in a NaOH aqueous solution to obtain OH - Selectively permeable membrane material with integrated protection against degradation.
[0016] Further, in step S1, in a round-bottom flask, 4-vinylbenzyl chloride and imidazole were mixed in a molar ratio of 1:1 and stirred for 8 hours.
[0017] Furthermore, in step S2, the mixture is fully stirred and dissolved at 50°C.
[0018] Further, in step S3, stirring is carried out at 50° C. for 1.5 h.
[0019] Furthermore, in step S4, the crosslinking agent is divinylbenzene, and the initiator is 2,2-azobis(2-methylpropionitrile).
[0020] Furthermore, in step S4, the amount of divinylbenzene used is 10 wt % of the amount of monomers used, and the amount of 2,2-azobis(2-methylpropionitrile) used is 1 wt % of the amount of monomers used.
[0021] Furthermore, in step S5, the polymer solution is heated to 80° C. under nitrogen protection and maintained for 8 hours to obtain a selectively permeable basement membrane solution.
[0022] Further, in step S6, drying is performed on a heating plate at 60° C. for 12 hours.
[0023] Further, in step S7, the mixture is immersed in 0.5 mol L -1 NaOH aqueous solution.
[0024] (III) Beneficial effects
[0025] The present invention proposes a selective permeable membrane material with integrated protection and degradation and a preparation method thereof. By introducing imidazole functional groups, the moisture permeability of the membrane material can be improved, and the membrane material can be given disinfection ability, while achieving the protection and barrier function of chemical warfare agents and the degradation of poisons. The selective permeable membrane material prepared by the present invention has good moisture permeability and comfort, and the water permeability is 3130g m -2 24h -1 , which can prevent the heat stress reaction from causing serious harm to the human body; it has excellent selective permeability and can play a good protective role, and the ion exchange capacity is about 2.14mmol g -1 The water / DMMP selectivity ratio is 106, and the water / CEPS selectivity ratio is 1780, which can effectively block chemical warfare agent simulants; the degradation half-life of DMNP is 7.3min, and it has a good function of degrading chemical warfare agents. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the selective permeable membrane material prepared in this example (in the figure, a is the surface part, and b is the cross-sectional part);
[0027] Figure 2 These are AFM images of selectively permeable membrane materials with different imidazole monomer contents prepared in this example (in the figure, a is M1, b is M2, c is M, d is M4, e is M5, and f is M6). DETAILED DESCRIPTION
[0028] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.
[0029] This embodiment provides a method for preparing a selective permeable membrane material with integrated protection against degradation, and the preparation method specifically comprises the following steps:
[0030] S1. In a round-bottom flask, 4-vinylbenzyl chloride VBC and imidazole Im were mixed in a molar ratio of 1:1 and stirred for 8h to prepare imidazole 4-vinylbenzyl chloride ImVBC monomer, and N,N-dimethylformamide was added to dissolve the monomer to obtain a first mixed solution;
[0031] In this example, different amounts of ImVBC monomer (0 g, 2.5 g, 6 g, 10 g, 16 g, 24 g) were prepared as needed.
[0032] S2. The polyvinylidene fluoride PVDF powder is added to the first mixed solution prepared in step S1, and stirred and dissolved at 50°C to obtain a second mixed solution;
[0033] S3. The methanol solution of tetramethylammonium hydroxide TMAH was added to the second mixed solution prepared in step S2, and stirred at 50 ° C for 1.5 h to obtain a third mixed solution;
[0034] S4. The crosslinking agent divinylbenzene DVB and the initiator 2,2-azobis(2-methylpropionitrile) AIBN are added to the third mixed solution prepared in step S3 to obtain a polymer solution; the amount of DVB is 10wt% of the amount of ImVBC, and the amount of AIBN is 1wt% of the amount of ImVBC;
[0035] S5. The polymer solution was heated to 80°C under nitrogen protection and maintained for 8 hours to obtain a selectively permeable basement membrane solution;
[0036] S6. The selective permeable base membrane solution is uniformly poured on a glass plate and dried on a heating plate at 60° C. for 12 h to obtain a selective permeable base membrane material;
[0037] S7. Soak the selective permeable base membrane material in 0.5 mol L -1 In NaOH aqueous solution, OH - PVDF-g-ImVBC, a selectively permeable membrane material with integrated protection against degradation.
[0038] The obtained membrane materials were named M1-M6, and their compositions are shown in Table 1.
[0039] Table 1 Composition of membranes with different imidazole contents
[0040]
[0041] Characterization and analysis of the prepared selective permeable membrane material PVDF-g-ImVBC:
[0042] like Figure 1 As shown in the figure, the surface and cross-sectional structures of the selective permeable membrane materials with integrated protection against degradation of pure PVDF and PVDF-g-ImVBC are shown. a is a surface SEM image of pure PVDF, showing a very smooth and dense surface. Figure b shows that the cross-section of PVDF-g-ImVBC is relatively flat and dense, without pore-forming defects, etc., which indicates that ImVBC is uniformly grafted on the PVDF molecules to form a uniform polymer.
[0043] like Figure 2As shown in the figure, the AFM phase image of the PVDF-g-ImVBC membrane shows the different ImVBC grafting amounts. As the ImVBC grafting amount increases, dark areas appear in the AFM phase image of the PVDF-g-ImVBC membrane, indicating that a hydrophilic-hydrophobic microphase separation structure is formed in the membrane material. The dark area represents the hydrophilic area, and the bright area represents the hydrophobic area. As the ImVBC grafting amount increases, the hydrophilic area increases, forming a continuous hydrophilic channel, which is conducive to the rapid transmission of water molecules in the membrane, thereby improving the water vapor permeability of the selective permeable membrane material with integrated protection and degradation.
[0044] The thermal properties of the selective permeable membrane materials with integrated protection and degradation of PVDF and PVDF-g-ImVBC were analyzed, including the study of crystallinity and thermal stability. Specifically, the crystallinity of PVDF and PVDF-g-ImVBC was characterized by differential scanning calorimetry (DSC). The results showed that the PVDF-g-ImVBC series membranes had similar melting point peaks, indicating the presence of crystalline regions in these membranes. This hydrophilic crystalline region helps to inhibit the expansion of the membrane material, maintain good mechanical properties, and enhance the chemical barrier properties of the membrane. In addition, the DSC results also showed that the crystallinity of the membrane decreased with the increase of the ImVBC grafting amount, which was due to the flexible side chains hindering the aggregation of the chain segments. Thermogravimetric analysis (TGA) characterized the thermal stability of PVDF and PVDF-g-ImVBC. The results showed that the initial degradation temperature of PVDF was about 400℃, while PVDF-g-ImVBC degraded in three different temperature ranges. The first degradation range was 50-160℃, mainly due to the evaporation of water molecules absorbed by the quaternary ammonium group. The second degradation range is around 220°C, corresponding to the degradation of quaternary ammonium groups. The third degradation range is 450-480°C, corresponding to the degradation of PVDF-g-ImVBC. Compared with pure PVDF, the degradation temperature of PVDF-g-ImVBC is slightly lower, which is due to the introduction of side chains that destroy the regular arrangement of the chain segments, resulting in a decrease in crystallinity.
[0045] IEC values were measured by titration. First, the membrane (0.2 g) was converted to the chloride form by soaking in a 1 molar NaCl aqueous solution for 24 hours. Second, the membrane was rinsed with deionized water and weighed using an analytical balance. Finally, the membrane was soaked in a 0.5 molar Na2SO4 aqueous solution for 24 hours. Cl was quantified by titration of a 0.1 molar AgNO3 aqueous solution using K2CrO4 as an indicator. - ions. The IEC value can be obtained by the mass of the chlorine-free dry film (W) as shown in formula (1). dry ) and the amount of AgNO3 consumed in the titration (V AgNO3 ×C AgNO3 ) calculation, where W wet and L wet refers to the weight and length of the wet film, respectively, and Wdry and L dry Refers to the weight and length of the dry film respectively.
[0046] IEC=(V AgNO3 ×C AgNO3 ) / W dry (1)
[0047] WU=(W wet –W dry ) / W dry ×100% (2)
[0048] LSR=(L wet –L dry ) / L dry ×100% (3)
[0049] In order to evaluate the vapor permeability performance of the selective permeable membrane material with integrated protection against degradation, a selective permeability test was performed based on the experimental method specified in the American Society for Testing and Materials (ASTM) E96-95 procedure. The membrane sample was located above an open test bottle, which contained a certain amount of permeate (such as water, DMMP or CEPS). The obtained permeate cell was placed in a constant temperature and humidity test chamber (35°C and 10% relative humidity) and weighed and recorded at intervals. When the weight loss of the permeate cell reached a constant value, the vapor transmission rate (VTR, g m-2-1) of the membrane can be calculated according to formula (4) by the slope of the weight-time curve obtained from the measured weight of the permeate cell. The vapor permeability (VP, mol m-1s-1) is calculated by formula (5). The vapor permeability ratio of water to DMMP or CEPS is defined as selectivity and calculated by formula (6). To ensure the accuracy of the experimental results, three parallel experiments were performed on the corresponding test of each membrane to obtain the average value.
[0050] VTR=W / (t×A) (4)
[0051] VP=VTR×L (5)
[0052] S=VP water / VP simulants (6)
[0053] Time t represents the time for the sample to be tested, A represents the sampling area of the sample, the effective test area of the membrane is about 6.28 square centimeters, L represents the thickness of the sample, S represents selectivity, VP water Represents water vapor permeability VP sumulants represents the simulant permeability.
[0054] The selectivity and permeability of the selectively permeable membrane material with integrated protection against degradation are shown in the following table.
[0055] Table 2 VTR of water and DMMP, VP of water and DMMP and selectivity of membrane
[0056]
[0057]
[0058] During the test, the membrane sample completely covers the test chamber, about 0.5 ml of the permeate liquid is dropped on the membrane sample, the upper part of the test chamber is sealed, and the lower chamber is ventilated with dry air at 300 mL / min to detect the liquid permeation under the permeate membrane sample. The permeate liquid passes through the membrane sample and enters the photoionization detector for detection. During the test, the permeate chamber is placed in a constant temperature room, and the test temperature is 35 ° C (when testing DMMP) or 20 ° C (when testing other toxic industrial chemicals). The selected toxic industrial chemicals include dichloromethane, acetone, ethyl acetate, toluene, acetonitrile, carbon disulfide, diethylamine, tetrahydrofuran and n-hexane.
[0059] DMNP is a neurotropic chemical warfare agent simulant. DMNP was used as a chemical warfare agent simulant to evaluate the degradation ability of PVDF-g-ImVBC.
[0060] The degradation effects of different protective and degradable selective permeable membrane materials on DMNP were studied by UV-Vis spectral analysis. The results showed that pure PVDF membrane had almost no degradation effect on DMNP, while PVDF-g-ImVBC protective and degradable selective permeable membrane material had a significant degradation effect on DMNP, and the degradation efficiency increased significantly with the increase of the relative content of quaternary ammonium groups in the membrane.
[0061] The degradation curve analysis showed that the degradation of DMNP conformed to the first-order reaction kinetics. The half-life of DMNP degradation in the selective permeable membrane material with integrated protection and degradation was significantly shorter than that of pure PVDF membrane, with M1 membrane being 23.1 minutes, M3 membrane being 16.6 minutes, M4 membrane being 7.3 minutes, and M5 membrane being 4.9 minutes. The results showed that with the increase of the relative content of quaternary ammonium groups in the selective permeable membrane material with integrated protection and degradation, the degradation ability of the selective permeable membrane material with integrated protection and degradation was enhanced, but it had a certain influence on the dimensional stability and mechanical properties of the selective permeable membrane material with integrated protection and degradation.
[0062] The microscopic separation structure of the selective permeable membrane material with integrated protection and degradation was analyzed by DPD simulation. By simulating and observing the microscopic separation structure of the selective permeable membrane material with integrated protection and degradation at different IEC values, it was found that with the increase of IEC value, the number and size of the hydrophilic areas formed increased. At the same time, the simulation results showed that with the increase of water content, the number and size of the hydrophilic areas formed also increased. In addition, with the increase of the grafting length of the quaternary ammonium group, the area and relative content of the hydrophilic area also increased. The simulation results verified the experimental observation that the selective permeable membrane material with integrated protection and degradation formed a microscopic separation structure of continuous water molecule transmission channels. At the same time, the simulation analysis also provides guidance for the experiment. The size of the hydrophilic area of the selective permeable membrane material with integrated protection and degradation can be controlled by adjusting the grafting length of the quaternary ammonium group, so as to prepare a reasonable separation membrane. The simulation study provides important guiding significance for the experiment.
[0063] By studying the effect of the relative content of quaternary ammonium groups in the selective permeability membrane material of PVDF-g-ImVBC on the selective permeability, degradation ability and physical and mechanical properties of the membrane material, it was found that the increase in the relative content of quaternary ammonium groups is conducive to the formation of microscopic separation structures, forming continuous water molecule transmission channels, and improving the degradation ability, selective permeability and moisture permeability of the membrane material. However, this will also reduce the dimensional stability and mechanical properties of the membrane material in a high humidity environment. Therefore, it is necessary to optimize the relative content of quaternary ammonium groups to achieve a balance of various properties in the application of chemical protective clothing.
[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A selective permeable membrane material with integrated protection and degradation, It is characterized in that The selective permeable membrane material with integrated protection against degradation is composed of a polyvinylidene fluoride main chain and a grafted imidazole 4-vinylbenzyl chloride polymerized side chain.
2. A method for preparing a selectively permeable membrane material with integrated protection and degradation, It is characterized in that The method for preparing the selectively permeable membrane material comprises the following steps: S1. 4-vinylbenzyl chloride and imidazole are mixed and stirred to prepare imidazole 4-vinylbenzyl chloride monomer, and N,N-dimethylformamide is added to dissolve the monomer to obtain a first mixed solution; S2. The polyvinylidene fluoride powder is added to the first mixed solution and stirred to dissolve to obtain a second mixed solution; S3. The methanol solution of tetramethylammonium hydroxide is added to the second mixed solution and stirred to obtain a third mixed solution; S4. The crosslinking agent and the initiator are added to the third mixed solution to obtain a polymer solution; S5. The polymer solution is heated under nitrogen protection to obtain a selectively permeable basement membrane solution; S6. The selective permeable base membrane solution is poured onto a glass plate and dried to obtain a selective permeable base membrane material; S7. Soak the selective permeable base membrane material in a NaOH aqueous solution to obtain OH - Selectively permeable membrane material with integrated protection against degradation.
3. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S1, in a round-bottom flask, 4-vinylbenzyl chloride and imidazole were mixed in a molar ratio of 1:1 and stirred for 8 h.
4. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S2, the mixture is stirred and dissolved at 50°C.
5. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S3, the mixture was stirred at 50°C for 1.5 h.
6. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S4, the crosslinking agent is divinylbenzene, and the initiator is 2,2-azobis(2-methylpropionitrile).
7. The method for preparing a selectively permeable membrane material according to claim 6, It is characterized in that In step S4, the amount of divinylbenzene used is 10 wt % of the amount of monomers used, and the amount of 2,2-azobis(2-methylpropionitrile) used is 1 wt % of the amount of monomers used.
8. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S5, the polymer solution is heated to 80°C under nitrogen protection and maintained for 8 hours to obtain a selectively permeable basement membrane solution.
9. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S6, drying is performed on a hot plate at 60°C for 12 hours.
10. The method for preparing a selectively permeable membrane material according to claim 2, It is characterized in that In step S7, the mixture is immersed in 0.5 mol L -1 NaOH aqueous solution.
Citation Information
Cited By
Selective permeable membrane composite material for chemical protective clothing and preparation method thereof
CN115897215A
A selectively permeable membrane composite for chemical protective clothing and a method of making the same
CN115897215B
